2022
DOI: 10.3389/fphys.2022.969854
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lncRNA/circRNA-miRNA-mRNA network to reveal potential functional ceRNAs in the skeletal muscle of chicken

Abstract: Skeletal muscle, comprising approximately 40% of body mass, is a highly complex and heterogeneous tissue serving a multitude of functions in the organism. Non-coding RNAs (ncRNAs) are known to participate in skeletal muscle development as critical regulators. However, the regulatory mechanisms of ncRNAs on chicken muscle traits are not well understood. In the present study, we collected the leg muscle from male embryos of Tibetan chicken at embryonic (E) 10 and E18 for RNA sequencing. A total of 6,583 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The stained muscle sections indicated that the embryonic muscle development pattern of the Chengkou mountain chicken closely resembled that of the Tibetan chicken and other local breeds in China ( 27 , 28 ). During E12, the muscle fibers were intermixed, and their distinct boundaries were indiscernible.…”
Section: Discussionmentioning
confidence: 76%
“…The stained muscle sections indicated that the embryonic muscle development pattern of the Chengkou mountain chicken closely resembled that of the Tibetan chicken and other local breeds in China ( 27 , 28 ). During E12, the muscle fibers were intermixed, and their distinct boundaries were indiscernible.…”
Section: Discussionmentioning
confidence: 76%
“…The leg muscles of geese are the main components of their skeletal muscles, and the production of goose meat is closely related to the growth and development of skeletal muscles (Pan et al, 2022). In this study, we investigated the regulatory mechanisms underlying skeletal muscle maturation by collecting samples of leg skeletal Frontiers in Physiology frontiersin.org muscles from Magang geese at 3 days and 3 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Some KEGG pathways for host genes of DECs in the experiment were the same as those of other studies. Pan et al [ 42 ] collected the leg muscle from male embryos of Tibetan chicken at embryonic (E) days 10 and 18 for RNA sequencing, and KEGG results for the host genes of DECs revealed that the enriched pathways involved Wnt signaling pathway and MAPK signaling pathway. The two terms were also enriched in the top 20 KEGG pathways in S14 vs. F14.…”
Section: Discussionmentioning
confidence: 99%